2021
DOI: 10.1161/strokeaha.120.030092
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion–Based Machine Learning Model Better Predicts Follow-Up Infarction in Patients With Acute Ischemic Stroke

Abstract: Background and Purpose: Prediction of infarct extent among patients with acute ischemic stroke using computed tomography perfusion is defined by predefined discrete computed tomography perfusion thresholds. Our objective is to develop a threshold-free computed tomography perfusion–based machine learning (ML) model to predict follow-up infarct in patients with acute ischemic stroke. Methods: Sixty-eight patients from the PRoveIT study (Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Thirteen studies adopted conventional ML algorithms including k-nearest neighbor classification (24), general linear regression (47), random forest (13,15,25,34,36,38,41,48) and gradient boosting (11,26,36) classifiers. Twentyfive studies proposed DL-based approaches consisting of artificial neural network (ANN) (31) and various types of convolutional neural network (CNN) with some of the noteworthy popular architectures, including 2D and 3D U-Net (12,16,17,27,28,39,40,43,49,50), residual network (ResNet) (12,29,37,50), recurrent residual U-Net (R2U-Net) (52) and DeepMedic (32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies adopted conventional ML algorithms including k-nearest neighbor classification (24), general linear regression (47), random forest (13,15,25,34,36,38,41,48) and gradient boosting (11,26,36) classifiers. Twentyfive studies proposed DL-based approaches consisting of artificial neural network (ANN) (31) and various types of convolutional neural network (CNN) with some of the noteworthy popular architectures, including 2D and 3D U-Net (12,16,17,27,28,39,40,43,49,50), residual network (ResNet) (12,29,37,50), recurrent residual U-Net (R2U-Net) (52) and DeepMedic (32).…”
Section: Resultsmentioning
confidence: 99%
“…It also drives the emergence of deep learning (DL) subfield, which has shown impressive results in medical image processing without prior selection for relevant features (9,10). Given the suboptimal performance of the conventional thresholding methods, initial studies attempted to apply ML and DL-based approaches and showed clear advantages for more precise prediction of the final infarct lesion from baseline imaging (11)(12)(13)(14)(15)(16)(17). These promising results inspired investigators to propose novel model methodologies by improving algorithm architectures, combining multi-modality input parameters, and applying in different clinical scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published DL models made use of the different perfusion parameters obtained by deconvolution as input parameters or the output derived from deconvolution as ground truth. 18,[32][33][34][35] Our model is completely free of deconvolution by using the source perfusion images as input and the final infarct as ground truth, which is a great advantage. In previous research, we showed that source perfusion scans as input parameters outperformed perfusion parameters derived from deconvolution in predicting final infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians may be concerned about the time consumption of processing and assessment of image data. Artificial intelligence (AI) technology, which is a rapidly burgeoning field, can provide fast and efficient automatic imaging analysis Through machine learning, a recent study demonstrated that CTP data could be used to estimate follow-up infarct in AIS patients [32]. The existing commercial software RAPID can automatically calculate the ASPECTS in AIS patients [33].…”
Section: Discussionmentioning
confidence: 99%